Genetic evidence points to distinct paternal settlers of the Faroe Islands and Iceland - Mann, Allison E.; Magnussen, Eyðfinn; Tillquist, Christopher R. (Frontiers in Genetics, 2024)
The Faroe Islands are a small archipelago located in the North Atlantic likely colonized by a small group of founders sometime between 50 and 300 CE. Post colonization, the Faroese people have been largely isolated from admixture with mainland and other island populations in the region. As such, the initial founder effect and subsequent genetic drift are likely major contributors to the modern genetic diversity found among the Faroese. In this study, we assess the utility of Y-chromosomal microsatellites to detect founder effect in the Faroe Islands through the construction of haplotype networks and a novel empirical method, mutational distance from modal haplotype histograms (MDM), for the visualization and evaluation of population bottlenecks. We compared samples from the Faroe Islands and Iceland to possible regional source populations and documented a loss of diversity associated with founder events. Additionally, within-haplogroup diversity statistics reveals lower haplotype diversity and richness within both the Faroe Islands and Iceland, consistent with a small founder population colonizing both regions. However, in the within-haplogroup networks, the Faroe Islands are found within the larger set of potential source populations while Iceland is consistently found on isolated branches. Moreover, comparisons of within-haplogroup MDM histograms document a clear founder signal in the Faroes and Iceland, but the strength of this signal is haplogroup-dependent which may be indicative of more recent admixture or other demographic processes. The results of the current study and lack of conformity between Icelandic and Faroese haplotypes implies that the two populations were founded by different paternal gene pools and there is no detectable post-founder admixture between the two groups.